Digitograph: A Mobile Digital Signatures Application for PDF file Using ED25519 and Asymmetric Encryption - Annisa Putri Wahyuni; Arif Bramantoro; Randi Rizal; Souhayla Elmeftahi (IAICO, 2025)
Digital signatures have become an essential tool in the digital era, providing a secure and efficient way to authenticate and verify the integrity of digital documents. The increasing need for remote and electronic transactions has led to a surge in the development of digital signature technology. This research presents a mobile application, Digitograph, designed to facilitate the process of digitally signing PDF files using ED25519 and Asymmetric Encryption. Several processes were employed to complete the Digitograph application, including a literature study to gather information and documents related to the development process. A research framework was prepared to ensure that the processes in the study were carried out in a directed and systematic manner. The development of the Digitograph application was successfully accomplished, with significant results demonstrating improvements in security, efficiency, and ease of use for digital signatures on PDF files. The following are some key aspects of the Digitograph application's development: 1) Enhanced security, 2) Performance and efficiency, 3) User-friendliness. Digital signatures using ED25519, and Asymmetric Encryption are one of the key technological applications in modern cryptography. ED25519 offers a high level of security, efficiency, and ease of use. This method enhances data security and significantly simplifies key management to address vulnerabilities in Asymmetric Encryption. The Digitograph application ensures the authenticity and integrity of documents, providing a practical solution in the digital era.